Principles or templates? The antecedents and performance effects of cross-border knowledge transfer - Oldroyd, James B.; Morris, Shad S.; Dotson, Jeffrey P. (Strategic Management Journal, 2019)
[Research Summary:Strategic use of codified knowledge across borders can be a vital component for project-based work. Analyzing 237 global consulting projects, we examine the performance effects of drawing upon different types of codified knowledge. We argue and find that using principle-based forms of knowledge is likely to improve a project's customer responsiveness, whereas using template-based knowledge increases a project's cost effectiveness. We also explore what drives project managers to select different forms of knowledge in the first place. Specifically, we find that manager experience drives knowledge principle use, whereas institutional distance drives knowledge template use. Taken together, our findings suggest that organizations need to carefully consider the performance implications of different types of codified knowledge that get used and understand what drives managers to use them. Managerial Summary:Managers understand the importance of knowledge management systems for projectbased work. Efforts are often made to ensure that knowledge is codified and disseminated throughout the firm so employees can draw upon them to complete their projects. Unfortunately, however, such efforts often lead to stockpiles of information that remain untapped and underutilized. This study seeks to answer two questions. First, how can managers influence workers to utilize different types of codified knowledge in the first place? Second, do different types of codified knowledge have differential effects on performance? We find that increased individual experience drives the use of knowledge principles, whereas workers that are more distant are more likely to use knowledge templates. At the same time, we find that when individuals draw upon knowledge principles it increases the customer responsiveness of their projects, whereas the use of knowledge templates increases cost effectiveness. This suggests that project-based firms should carefully consider codifying both knowledge templates as well as knowledge principles and consider how to incentivize workers to draw upon these different forms of knowledge.]